Innovative Synergy: Leveraging Motivation and Discipline for Peak Employee Performance - Yayu Kusdiana; Arie Yusnelly; Nanda Suryadi (Yayasan Pendidikan Islam Al-Matani, 2024)
This study aims to determine the effect of motivation and work discipline on employee performance, both partially and simultaneously, at PT Putra Supra Jaya, specifically in the Langgam plantation area located in Riau province. A quantitative approach was employed for this research. The population consisted of 105 employees, with a sample size of 52 respondents selected using purposive sampling technique. The results indicate that both motivation and work discipline have a positive and significant impact on employee performance at PT Putra Supra Jaya in the Langgam plantation area.